Green and Oolong Tea Extracts With Different Phytochemical Compositions Prevent Hypertension and Modulate the Intestinal Flora in a High-Salt Diet Fed Wistar Rats - Ye, Xin; Tang, Xiaojuan; Li, Fanglan; Zhu, Jiangxiong; Wu, Meirong; Wei, Xinlin; Wang, Yuanfeng (Frontiers in Nutrition, 2022)
Green tea (GT) and oolong tea (OLT) are widely consumed beverages, and their preventive and regulatory effects on hypertension have been reported. However, the interventional effects of GT and OLT on hypertension induced by a high-salt diet and its mechanism have not been fully explored. This study evaluated the anti-hypertensive effects of GT and OLT and their underlying mechanisms. The in vivo anti-hypertensive effects of GT and OLT and their capability to prevent hypertension and regulate the intestinal microbiota in Wistar rats fed with a high-salt diet were evaluated. Our results show that GT and OLT supplementations could regulate oxidative stress, inflammation, gene expression, and parameter levels related to blood pressure (BP), and prevent the increase in BP induced by a high-salt diet. Both GT and OLT boosted the richness and diversity of intestinal microbiota, increased the abundance of beneficial bacteria and reduced the abundance of harmful bacteria and conditionally pathogenic bacteria, and regulated the intestinal microbial metabolism pathway related to BP. Among them, OLT presented better effects than GT. These findings indicate that GT and OLT can prevent hypertension caused by high-salt diets, which may be due to the regulation of intestinal flora by GT and OLT.